2004
DOI: 10.1159/000078301
|View full text |Cite
|
Sign up to set email alerts
|

Arteriolar Endothelial Dysfunction Is Restored in Ischaemic Muscles by Chronic Electrical Stimulation

Abstract: Chronic intermittent electrical stimulation (15 min on, 85 min off, seven times per day) eliminated endothelial dysfunction of pre-capillary arterioles in ischaemic rat ankle flexor muscles. Responses to acetylcholine were restored from constriction to dilation, and the reduced dilation to bradykinin was corrected by 1 week of stimulation. Administration of the NOS inhibitor Nω-nitro-L-arginine for 1 week impaired arteriolar reactivity in a similar way to ischaemia, and dilator function was likewise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 71 publications
(56 reference statements)
0
23
1
2
Order By: Relevance
“…Other studies (34,56) have shown that perfusion subsequent to femoral artery occlusion is not correlated with capillarity. Studies have shown that chronic reductions in flow and pressure can result in enhanced constriction and inward remodeling characterized by wall thinning (1,6,8,17,19,41,49,50,64,67), characteristics that occur in human critical limb ischemia (17)(18)(19). Thus, the profound decrease in distal microvascular flow and pressure could result in similar decompensatory events in the precapillary arterioles and small arteries that control the majority of microvascular resistance (3,27,42,77).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (34,56) have shown that perfusion subsequent to femoral artery occlusion is not correlated with capillarity. Studies have shown that chronic reductions in flow and pressure can result in enhanced constriction and inward remodeling characterized by wall thinning (1,6,8,17,19,41,49,50,64,67), characteristics that occur in human critical limb ischemia (17)(18)(19). Thus, the profound decrease in distal microvascular flow and pressure could result in similar decompensatory events in the precapillary arterioles and small arteries that control the majority of microvascular resistance (3,27,42,77).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, chronic ischemia leads to vasodilatory dysfunction. Ischemic arterioles in the lower leg have impaired functional vasodilation, which could be explained by impaired endothelial-dependent dilation [69,70]. Similar results were found in rat collateral arteries in vitro [71].…”
Section: Aim 2: Future Recommended Modificationsmentioning
confidence: 61%
“…Also, with improvements made in superfusion, the effects of age using cell-specific vasoactive agents can be addressed. Exercise is also a possible treatment to be attempted, as previous research has showed improvement in endothelial function [41,70,71] following exercise. It is still unclear what specifically impairs vascular function in ischemic conditions; it is the goal of this research to solve those questions.…”
Section: Final Conclusionmentioning
confidence: 99%
“…Thus, the previously mentioned beneficial effects of LFES on vascular function are most probably related to the effect of increased pulsatile flow on the vessel's endothelial layer. 54,55 It is likely that the LFESinduced changes in blood flow by long-term electrical stimulation are related to modification of endothelial function, and thus may be mostly NO-dependent, but as mentioned earlier, additional mechanisms cannot be excluded, especially the possible growth enhancement of new vessel collaterals, as occurs after physical exercise training. 56 The contribution of LFES on vascular remodelling observed in this study may be seen in the insignificant increase of the inner diameter of the right femoral artery at the end of the 6 th week of stimulation.…”
Section: Discussionmentioning
confidence: 99%